Analisis Buku Ajar Sejarah Kebudayaan Islam Menurut Badan Standar Nasional Pendidikan - Imam Fahrudin (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2020)
This study was conducted to find out how the feasibility of the ministry of religius Affairs of the republik of Indonesia with the criteria of teaching book According to BNSP. This study is considered important which given the feasibility of teaching book should refer to the criteria of BNSP. The research was conductedÂ With the qualitative approach and used literature research in data mining. The research method is conducted in three phases, they are:1) analyzing students books SKI class XIII MTS, 2) develop instrument of teaching book criteria According to BNSP, 3) relevant data collection, grouping data, provide assessment and explanation in narative. The feasibility rate of the teaching book in value with the predicate is less decent, decent enough, decent, and very decent. This study obtained the result that the conformity of Islamic cultural history book. According to BNSP has a very decent criteria to be used as teaching materials with the value of 93,02.